Preparation of cobalt/carbon-xerogel for heterogeneous oxidation of phenol - Sun, Hongqi; Tian, Hu-Yong; Hardjono, Y.; Buckley, Craig; Wang, Shaobin (Elsevier BV, 2012)
Two catalysts of Co oxide loaded on carbonxerogel (CX) were prepared by either in situ Co ion doping (Co/CX-G) or impregnation (Co/CX-I). The samples were characterised by N2 adsorption, X-ray diffraction (XRD), scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM–EDS), temperature programmed oxidation (TPO)–differential scanning calorimetry (DSC) and temperature programmed desorption (TPD)–DSC. Their performances in adsorption of phenol and heterogeneousoxidation of phenol using sulphate radical in aqueous solution were investigated. It was found that loading of Co oxide on carbonxerogel reduced the adsorption capacity of phenol. Co/CX samples prepared by the different methods exhibited varying activities in heterogeneousoxidation of phenol by sulphate radical. Kinetic studies demonstrated that Co/CX presented the first-order kinetics and the activation energies were obtained as 62.9 and 48.3 kJ/mol for Co/CX-G and Co/CX-I, respectively.